Alla scoperta dei bassorilievi di Faida. Il Kurdish-Italian Faida Archaeological Project (KIFAP) - Savioli, Alberto; Murana, Federica (Archeomatica, 2023)
Between 2019 and 2022, the team of the Kurdish-Italian Faida Archaeological Project (KIFAP) found thirteen Assyrian rock reliefs in Faida, Northern Iraqi Kurdistan. The archaeological mission was conducted by Professor Daniele Morandi Bonacossi from the Department of Humanities and Cultural Heritage (DIUM) of the University of Udine together with the Directorate of Antiquities of Duhok. The finding of the first ten rock reliefs of the VIII Century BC earned the title of the most important archaeological discovery of 2019, winning the prestigious 2022 International Archaeological Discovery Award Khaled al-Asaad. Four years later, on October 16th, 2022, the Faida Archaeological Park was officially opened, the first of its kind in Iraq.